Characteristics of aquatic biospheres on temperate planets around Sun-like stars and M dwarfs. Issue 3 (4th March 2021) - Lingam, Manasvi; Loeb, Abraham
ABSTRACT: Aquatic biospheres reliant on oxygenic photosynthesis are expected to play an important role on Earth-like planets endowed with large-scale oceans insofar as carbon fixation (i.e. biosynthesis of organic compounds) is concerned. We investigate the properties of aquatic biospheres comprising Earth-like biota for habitable rocky planets orbiting Sun-like stars and late-type M dwarfs such as TRAPPIST-1. In particular, we estimate how these characteristics evolve with the available flux of photosynthetically active radiation (PAR) and the ambient ocean temperature ( TW ), the latter of which constitutes a key environmental variable. We show that many salient properties, such as the depth of the photosynthesis zone and the net primary productivity (i.e. the effective rate of carbon fixation), are sensitive to PAR flux and TW and decline substantially when the former is decreased or the latter is increased. We conclude by exploring the implications of our analysis for exoplanets around Sun-like stars and M dwarfs.